2018
DOI: 10.22551/2018.19.0502.10124
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of neonatal-onset infantile myofibromatosis with metastatic recurrence in adulthood

Abstract: Infantile myofibromatosis (IM) is a rare mesenchymal disorder, typically observed during infancy and characterized by the development of myofibroblastic tumors within skin, muscle, bone or viscera. In most cases, spontaneous regression of the lesions occurs before the age of four, however therapeutic tools such as surgery and chemotherapy sometimes need to be implemented. Metastatic recurrence of this condition is very rare. We report the case of a newborn infant with multicentric IM involving the skin, intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Recurrent IM is rare and it has been reported in 17 patients in the literature (Table 3). 14,26,[34][35][36][37][38][39][40][41] Noteworthy is the high recurrence received chemotherapy of various combinations 34,38 or spontaneously regressed. 14,41 As demonstrated by our Patient 2, recurrence can be treated with the same chemotherapeutic regimen used for the treatment of the initial disease.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Recurrent IM is rare and it has been reported in 17 patients in the literature (Table 3). 14,26,[34][35][36][37][38][39][40][41] Noteworthy is the high recurrence received chemotherapy of various combinations 34,38 or spontaneously regressed. 14,41 As demonstrated by our Patient 2, recurrence can be treated with the same chemotherapeutic regimen used for the treatment of the initial disease.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Our review of the literature revealed 15 patients with GI involvement (Table 2). 9–12,14,15,22– Interestingly, only four of them presented as a solitary lesion, while all the others were part of the generalized form of disease with visceral involvement. Pancreas involvement was found in four out of a total of 15 reported patients (Table 2).…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) Multicentric/generalized IM is generally considered a multifocal disorder. Metastases have anecdotally been reported in the past[53]. It is conceivable that certain lesions represent metastases rather than multiple inde-…”
mentioning
confidence: 99%